INSTITUTIONAL OWNERSHIP AND CAPITAL STRUCTURE: A CASE OF UK FIRMS - Nguyen, Anh Quynh (2020)
This study investigates the influence of institutional ownership on the target leverage and the capital structure adjustment speeds of UK firms under the framework of dynamic trade-off theory. I draw the financial data from 294 non-financial and -utility firms of FTSE All Shares Index over 2010-2019 period. To overcome endogenous problems arising from the dynamic nature and the simultaneous relationships between capital structure and other firm-specific characteristics, the main approach in this dissertation is Generalized Method of Moments. The empirical models reveal that institutional ownership is an important determinant of the desired book debt ratios in UK firms. Meanwhile, I find no evidence that institutional ownership affects the market debt ratios in these firms. The removal of institutional holdings from the initial regressions suggests that this variable should only serve as instrumental variables for the endogenous variables in the market debt ratios’ model rather than a regressor like the book-based one. At the same time, the partial adjustment models show that UK firms rapidly diminish 39.3% of the gap between the actual book debt ratios and the target levels each year, while the number for the market-based indicator is significant lower at 22.9%. Consistent with the regressions of fixed-effects models, the dynamic models expose that profitability negatively correlates with both book- and market-based indicators, whereas size positively relates to the book one only. By assuming capital structure adjustment speeds are a function of institutional holdings, I document that there is no correlation between these two factors.